How Consumers Price Fresh Whole Milk Label? - CHANCHAROENCHAI, Kanokwan (Journal of Environmental Management and Tourism, 2017)
As it recently happens in the Thai market, the label or information on the UHT package is unclear whether it is made of fresh or powdered milk. In order to allow consumers to perceive the clear distinction between fresh and combined milk, the clear and government-certified label should be introduced. The questionnaires are constructed to draw consumers’ behavior and their utility from buying fresh milk with certified label. The 540 respondents, living in Bangkok and having experiences in buying or drinking UHT milk, are representatives in this investigation. There are 171 respondents or 31.71% who show their unwillingness to pay even though most of them agree to the concept of market differentiation between fresh and combined milk. Based on the probity analysis, there are six factors that significantly explain the change in the possibility to pay for label. According to the finding, the weighted mean of MWTP is 1.96 Thai baht per 250 ml. Thai government must provide proactive strategies on the dissemination of information about milk nutrition and partial subsidy to keep consumers' demand for fresh milk. This increase in fresh milk demanded not only improves the consumers’ nutrition, but also implicitly supports the farmers’ welfare and trade balance.